Sensor performance specifications. - Bernstein, D.S.
The author explains sensor specifications which quantify the ability of sensor to provide measurements of physical variables. Sensor manufacturer typically provide information about sensor specifications in the form of a specification sheet. The concepts described will help one interpret the information on a specification sheet. They can be applied to all branches of science and engineering, not just control systems. However, the systems approach of control engineers provides a unique perspective on these topics and associated issues
Keywords: Control systems; Dynamic response; Impedance; Performance specifications; Sensitivity; Sensors; Static response